2019
DOI: 10.1016/j.heliyon.2019.e01448
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-by-environment interaction of newly-developed sweet potato genotypes for storage root yield, yield-related traits and resistance to sweet potato virus disease

Abstract: Genotype-by-environment interaction analysis is key for selection and cultivar release, and to identify suitable production and test environments. The objective of this study was to determine the magnitude of genotype-by-environment interaction (GEI) for storage root yield, yield-related traits and sweet potato virus disease (SPVD) resistance among candidate sweet potato genotypes in Tanzania. Twenty-three newly bred clones and three check varieties were evaluated across six diverse environments using a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 39 publications
5
32
1
6
Order By: Relevance
“…The whole mating pairs produced many compatible pairs and many seeds or seedlings for base population breeding. This is in line with the research of Ngailo, Shimelis, Sibiya, Mtunda, & Mashilo (2019) and Rukundo, Shimelis, Laing, & Gahakwa (2017) that reported on a recombination through sexual reproduction can bring four new characters with a worthy combination of significant traits and a single seed can give rise to a potentially commercial variety.…”
Section: Seeds Numbersupporting
confidence: 87%
“…The whole mating pairs produced many compatible pairs and many seeds or seedlings for base population breeding. This is in line with the research of Ngailo, Shimelis, Sibiya, Mtunda, & Mashilo (2019) and Rukundo, Shimelis, Laing, & Gahakwa (2017) that reported on a recombination through sexual reproduction can bring four new characters with a worthy combination of significant traits and a single seed can give rise to a potentially commercial variety.…”
Section: Seeds Numbersupporting
confidence: 87%
“…Several strategies could be applied in plant epidemiology to control plant viruses by taking into consideration virus–vector and virus–host interactions. To combat viral diseases such as sweet potato virus disease, the most common and effective strategy to date has been to select resistant sweet potato genotypes (Tairo et al , 2005; Ngailo et al , 2019). However, there are few sweet potato cultivars resistant to sweet potato virus disease in the field, especially in East Africa where there is a great demand for virus‐resistant sweet potatoes for subsistence farming.…”
Section: Discussionmentioning
confidence: 99%
“…Vimala and Nair (1988) observed that for 20 sweetpotato cultivars, the segregation patterns of several morphological characters showed continuous and overlapping variation, indicating the quantitative nature for the morphological traits they studied. Many of the genotype · environment interactions for storage root characteristics and yield have been studied in sweetpotato, but little is known concerning environmental effects on leaf characteristics (Gr€ uneberg et al, 2005;Laurie and Booyse, 2015;Mwololo et al, 2009;Ngailo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%